Tracking finance for locally led climate action in Ghana: Existing initiative, challenges and recommendations - Callaghan, Charles; Binge, Brenda; Chilambe, Pedro; Lauriciano, Rabeca (2025)
This report reviews existing initiatives, gaps, and recommendations for improving the tracking of finance that supports locally led climate action in Ghana. It highlights the importance of assessing not only the quantity of climate finance reaching local levels but also the quality of that finance—using emerging metrics such as subsidiarity (where decision-making authority sits), flexibility (ability to adjust funding to local priorities and changing conditions), patience (longer-term commitments that enable institutional learning and adaptation), and predictability (reliable funding that supports planning and continuity).